Q. 134.1( 11 Votes )

# Find the value of

Answer :

Let, f (x) = k2x- kx+ 3kx k

By factor theorem,

If (x – 3) is a factor of f (x) then f (3) = 0

k2 (3)3 – k (3)2 + 3 k (3) – k = 0

27k2 – 9k + 9k – k = 0

k (27k – 1) = 0

k = 0 or (27k – 1) = 0

k = 0 or k = Hence, (x – 3) is a factor of f (x) when k = 0 or k = .

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Division of Polynomials46 mins  Quiz- Test what you Know Part 246 mins  Polynomials- Introduction45 mins  Identities Ke Master Bane47 mins  Quiz- Test what you Know64 mins  Conservation of Energy41 mins  Pair of Angles29 mins  Complete Basics of Class 9 Chemistry - I35 mins  Equations of Motion41 mins  Graphical Representation of Motion - II39 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar